QUALITY INFORMATION MANAGEMENT IN PUBLIC ADMINISTRATION AUTHORITIES - Semenenko К.A. (Pressing Problems of Public Administration, 2016)
Investigated improvement of quality management information to the authorities; discussed the conceptof “information, which is used in government”; highlight the speci c properties of information that areimportant to improve its quality.